Robotics in oral surgical procedures: Integrative review (Research, Society and Development, 2021)
Robots are a technological innovation adapted to use in surgical procedures of the most varied areas, assisting health professionals in fulfilling their role. When associated with dentistry, they have applicability in several areas such as oncology and implantology. The objective of this work was to carry out an integrative review of the current literature on robotic surgical procedures in dentistry, highlighting its techniques, indications, advantages and disadvantages. A research of articles had been done on the electronic databases CAPES, PubMed and MEDLINE, using the descriptors: robotic surgical procedures, dentistry, oral surgery, indexed in the period from 2015 to 2020 that dealt with case reports, literature reviews, in vivo studies that report the use of robots in dental surgical procedures, feasibility studies and clinical trials. After the eligibility criteria, 18 articles published in English were analyzed. Studies have shown that the use of robots in dental surgery brings more precision to the procedure, decreasing tissue loss, reducing the possibility of hemorrhage, reducing possible residual scarring, and post-surgical. Robotic surgery in several areas of dentistry has already demonstrated high reliability, allowing from better precision to greater assertiveness, in addition to providing less invasive surgical access with damage tissue adjacent to the relatively smaller area of operation, optimizing the surgical procedure.